2020
DOI: 10.1101/2020.12.14.422737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Requires Cholesterol for Viral Entry and Pathological Syncytia Formation

Abstract: SummaryMany enveloped viruses induce multinucleated cells (syncytia), reflective of membrane fusion events caused by the same machinery that underlies viral entry. These syncytia are thought to facilitate replication and evasion of the host immune response. Here, we report that co-culture of human cells expressing the receptor ACE2 with cells expressing SARS-CoV-2 spike, results in synapse-like intercellular contacts that initiate cell-cell fusion, producing syncytia resembling those we identify in lungs of CO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 157 publications
(216 reference statements)
4
30
0
Order By: Relevance
“…Using VLPs pseudotyped with WT or acylation deficient Spike, as well as SARS-CoV-2 virions produced from cells silenced for ZDHHC8/9/20 expression, we could show that acylation greatly enhances viral fusion and infectivity. Our findings are fully consistent and complementary to those by Brangwynne and co-workers who recently identified, through a screening approach, that cholesterol present in the membrane of VLPs is critical for Spike-mediated fusion (Sanders et al, 2020). Our study shows that S-acylation, and the ZDHHC20 enzyme in particular, constitutes a promising drug target for coronavirus infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using VLPs pseudotyped with WT or acylation deficient Spike, as well as SARS-CoV-2 virions produced from cells silenced for ZDHHC8/9/20 expression, we could show that acylation greatly enhances viral fusion and infectivity. Our findings are fully consistent and complementary to those by Brangwynne and co-workers who recently identified, through a screening approach, that cholesterol present in the membrane of VLPs is critical for Spike-mediated fusion (Sanders et al, 2020). Our study shows that S-acylation, and the ZDHHC20 enzyme in particular, constitutes a promising drug target for coronavirus infection.…”
Section: Discussionsupporting
confidence: 91%
“…Coronaviridae Spike proteins contain a conserved cysteine-rich stretch of amino acids in their cytosolic tail ( Figure 2A) (Gelhaus et al, 2014;Thorp et al, 2006). SARS-CoV-2 Spike has 10 cysteines within its first 20 cytosolic amino acids ( Figure 2A) and was recently highlighted as one of the most cysteine-rich proteins encoded by animal viruses (Sanders et al, 2020). To study the relative importance of these residues, we generated four mutants changing groups of 2-3 adjacent cysteines to alanine ( Figure 2A).…”
Section: Rapid and Extensive Acylation During Spike Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although SARS-CoV-2 and most other coronaviruses do not bud from the cell surface, some S protein is found on the surface of infected cells. Consistent with this, infected cells have been observed to fuse with neighbouring cells to form large multinucleate cells or syncytia [15][16][17][18][19] . Thus, S must exit the ER to reach the ERGIC and later Golgi compartments, with some travelling all the way to the cell surface but the majority being retained at the site of viral budding.…”
supporting
confidence: 55%
“…It has recently been reported that syncytia formation by SARS-CoV-2 S can induce pyroptosis, and it has been proposed for other viral-mediated fusion events that cell death following syncytia formation can affect immune responses 60,61 . All this has led to an interest in the possibility that syncytia formation by SARS-CoV-2 is a potential target for therapeutic strategies 18,62 . Indeed, the process appears entirely dependent on the cell surface protease TMPRSS2 to make the activating S2' cleavage, whereas viral entry can be facilitated by either TMPRSS2 or lysosomal cathepsins 11,17 .…”
Section: Discussionmentioning
confidence: 99%